Thermodynamics of Deca-alanine Folding in Water - Hazel, Anthony (American Chemical Society, 2014)
[Image: see text] The determination of the folding dynamics of polypeptides and proteins is critical in characterizing their functions in biological systems. Numerous computational models and methods have been developed for studying structure formation at the atomic level. Due to its small size and simple structure, deca-alanine is used as a model system in molecular dynamics (MD) simulations. The free energy of unfolding in vacuum has been studied extensively using the end-to-end distance of the peptide as the reaction coordinate. However, few studies have been conducted in the presence of explicit solvent. Previous results show a significant decrease in the free energy of extended conformations in water, but the α-helical state is still notably favored over the extended state. Although sufficient in vacuum, we show that end-to-end distance is incapable of capturing the full complexity of deca-alanine folding in water. Using α-helical content as a second reaction coordinate, we deduce a more descriptive free-energy landscape, one which reveals a second energy minimum in the extended conformations that is of comparable free energy to the α-helical state. Equilibrium simulations demonstrate the relative stability of the extended and α-helical states in water as well as the transition between the two states. This work reveals both the necessity and challenge of determining a proper reaction coordinate to fully characterize a given process.